How would one complete the square: x^2 + 6x +x2+6x+ _?

3 Answers
Mar 29, 2018

+9+9

Explanation:

"to "color(blue)"complete the square"to complete the square

• " add "(1/2"coefficient of the x-term")^2" to" add (12coefficient of the x-term)2 to
x^2+6xx2+6x

rArrx^2+6xcolor(red)(+3)^2=x^2+6x+9=(x+3)^2x2+6x+32=x2+6x+9=(x+3)2

Mar 29, 2018

x^2+6x+9-9=(x+3)^2-9x2+6x+99=(x+3)29

Explanation:

To complete square one is basically doing

a^2+2ab+b^2=(a+b)^2a2+2ab+b2=(a+b)2
or
a^2-2ab+b^2=(a-b)^2a22ab+b2=(ab)2

We can see that x^2=a^2x2=a2 and
2ab=6x2ab=6x

So all we need to condense this into (a+b)^2(a+b)2 is a b^2b2 term
We know that
2b=62b=6 as x=ax=a
so b=3b=3
and b^2=9b2=9

So if we put the b^2b2 term in we get

x^2+6x+9-9=(x+3)^2-9x2+6x+99=(x+3)29

We include the +-9±9 because we have to net add nothing to the equation so 9-9=099=0 so we really haven't added anything

Mar 29, 2018

x^2+6x+color(red)(9)=(x+3)^2x2+6x+9=(x+3)2

Explanation:

We have,

x^2+6x+square?.

First Term =F.T.=x^2

MiddleTerm =M.T.=6x

Third Term =T.T.=square?

Let us use the Formula:

color(red)(T.T.=(M.T.)^2/(4xx(F.T.))=(6x)^2/(4xx(x^2))=(36x^2)/(4x^2)=9

Hence,

x^2+6x+color(red)(9)=(x+3)^2

I think no need to double check the answer.Please see below.

e.g.

(1)a^2+2ab+color(red)(b^2)=(a+b)^2

T.T.=(2ab)^2/(4xxa^2)=(4a^2b^2)/(4a^2)=color(red)(b^2

(2)a+2sqrt(ab)+color(red)(b)=(sqrta+sqrtb)^2

T.T.=(2sqrt(ab))^2/(4xxa)=(4ab)/(4a)=color(red)(b

(3)613089x^2+1490832xy+color(red)(906304y^2)= (783x+952y)^2

T.T.=(1490832xy)^2/(4xx613089x^2)= (2222580052224x^2y^2)/(2452356x^2)=color(red)(906304y^2